Modeling the Nonlinear Oil-Water Two-Phase Flow Behavior for a Multiple-Fractured Horizontal Well in Triple Media Carbonate Reservoir (Advances in Applied Mathematics and Mechanics, 2018)
Carbonate reservoir is one of the important reservoirs in the world. Becauseof the characteristics of carbonate reservoirs, horizontal well and acid fracturing havebecome a key technology for efficiently developing carbonate reservoir. Establishingcorresponding mathematical models and analyzing transient pressure behaviors ofthis type of well-reservoir configuration can provide a better understanding of fluidflow patterns in formation as well as estimations of important parameters.A mathematical model for an oil-water two-phase flow fractured horizontal well intriple media carbonate reservoir by conceptualizing vugs as spherical shapes is presentedin this article. A semi-analytical solution is obtained in the Laplace domainby using source function theory, Laplace transformation and superposition principle.Analysis of transient pressure responses indicates that nine characteristic flow periodsof fractured horizontal wells in triple media carbonate reservoir can be identified.Parametric analysis shows that water saturation of matrix, vug and fracture systemand fracture half-length, fracture number and fracture spacing can significantly influencethe transient pressure responses of fractured horizontal wells in triple mediacarbonate reservoir. The model presented in this article can be applied to obtain importantparameters pertinent to reservoir or fracture by type curve matching and it canalso provide useful information for optimizing fracture parameters.